Linear polarization of x rays due to dielectronic recombination into highly charged ions. (August 2015) - Shah, Chintan; Jörg, Holger; Hu, Zhimin; Bernitt, Sven; Bekker, Hendrik; Blessenohl, Michael A.; Hollain, Daniel; Weber, Sebastian; Dobrodey, Stepan; Fritzsche, Stephan; Surzhykov, Andrey; López-Urrutia, José R Crespó; et al.
Synopsis: The linear polarization of x rays produced by dielectronic recombination into highly charged ions was for the first time measured at an electron beam ion trap using a newly developed Compton polarimeter. The experimental results open a possibility for diagnostics of anisotropies of hot plasmas. We also demonstrate a high sensitivity of the x-ray polarization to the Breit interaction.